Ontologias para anotação semântica em mídias: Uma construção colaborativa de redes de conhecimento do patrimônio cultural (Advances in Knowledge Representation, 2021)
This article aims to present a systematic survey of ontological models that are being commonly used as annotation standards in diverse media, especially addressed to projects of integration of cultural collections in a connected open data environment and involving as platforms of the Wikimedia Foundation such as Wikipedia, Wikimedia Commons and Wikidata, which seeks to expand the user base and the collaborative production of its information resources to expand the dissemination of heritage collections, make explicit what is generated in its known collections, and, therefore, value and democratize culture in the network society. This is theoretical and qualitative research, exploratory and descriptive, using as a method a systematic literature review in specialized databases in the fields of Information and Computer Science, together with the use of analytical dimensions to organize constituent elements of ontologies listed in the study. As a result, it presents a systematic analysis of CIDOC CRM, CRMdig, Linked Art, EMD and FRBRoo conceptual ontology models, showing how these document standards are being used as forms of representation of multimedia knowledge in the context of cultural heritage and how they organize in its structures, multimedia metadata (independent, dependent and descriptive of content) and provenance (origin and production methods) for the description of cultural objects in different contexts and needs. The models are presented as good candidates for reuse, especially in projects aimed at integrating cultural heritage collections in a Linked Open Data environment and involving the wiki's ecosystem.